Managing physical hazards on construction site - Siti Norlizah, Haji Saiman (2010)
Physical hazards on construction site are defined as those types of hazards that can harm a worker from external sources on construction site. Physical hazards on construction site is contribute high accidental and cause death. This paper based on study that has been conducted which involves types of physical hazards and consequences of physical hazards towards the workers on construction site Besides, the solution in managing the physical hazards on construction site is included. The study is focused at Kuantan, Pahang and Kuching, Sarawak areas. This study will increase awareness among the workers in the construction site in delivering a project responsibility by also focusing to physical hazards factors Two (2) methods have been used to achieve the objectives of this study which are questionnaire and interview. Thirty six (6) respondents are given their feedback answering the questionnaires. Data and results are analyzed using two (2) methods which are Microsoft Excel and Statistical Package for Social Sciences Software (SPSS).The data collected from the questionnaire survey have been analyzed using Average Index (Al). As conclusion, types of physical hazards on construction site are including noise, radiations, excessive temperature and pressure, mechanical, electrical and illuminations. There are Jew consequences caused by physical hazards which are fatigue, hearing loss, spinal injury, less sensitivity to touch and temperature, dry skin and eyes, cancer, heat exhaustion heat stroke s burns, crushing, breaking, cutting, painful shock, death and dazzle. This study result shows the popular solutions in managing physical hazards on construction site by respondents are management commitment and leadership by employer in safety and also accident prevention programs.